11. CHARACTERISTICS OF GLOBAR PNEUMONIA AT THE RESPIRATORY DEPARMENT 1 IN CHILDREN’S HOSPITAL 2 (Vietnam Journal of Community Medicine, 2025)
Objectives: A survey of the clinical characteristics, paraclinical findings, microbial agents, complications, and the treatment outcomes of the lobar pneumonia at the Respiratory Department 1 in Children’s Hospital 2.Method: A prospective case series report study.Results: One hundred- thirty one (131) patients were described.The median age of onset was 5 years. Among the patients with globar pneumonia, 96.9 % had completed the full Hib vaccination schedulem, while 71% had not completed the pneumococcal vaccination. Most patients had normal white blood cell counts and neutrophil percentages in peripheral blood for their age. Elevated CRP levels (>20mg/dl) were found in 61.8% of globar pneumonia cases. On chest X-rays, right lower lobe pneumonia was the most commonly observed. The bacterial causes of globar pneumonia isolated through nasopharyngeal cultures had a low positive rate of 12.2%, with S. aureus being the most commonly identified organism. Other bacteria included H. influenzae and S. pneumoniae. Complications were present in 15.3% of globar pneumoniaa cases, most commonly respiratory failure and sepsis, followed by lung consolidation, pleural empyema and necrosis. A total of 60.5% of cases responded to initial antibiotic treatment, while 39.5% did not respond and required either a change or addition of antibiotics. Among these, Levofloxacin was the most frequently substituted antibiotic (62.2%), which correlated with a 66.4% positive rate for IgM serology diagnostic for Mycoplasma pneumoniae.Conclusion: Lobar pneumonia is a condition that can cause severe complications, with the leading bacterial pathogens being Staphylococcus aureus and Streptococcus pneumoniae. Therefore, initial antibiotic treatment for lobar pneumonia should cover both of these pathogens.
Keywords: globar pneumonia.